Experimental investigation on BFRCM confinement of masonry cylinders and comparison with BFRP system. (23rd August 2021) - D'Anna, Jennifer; Amato, Giuseppina; Chen, Jian Fei; Minafò, Giovanni; La Mendola, Lidia
Highlights: The performance of BFRCM-confined cylinders is investigated and compared with that of BFRP-confined cylinders. The effect of the number of vertical mortar joints in the masonry is studied. The influence of the number of BFRCM reinforcing layers is analysed. Traditional measuring instruments are integrated with DIC technique. Abstract: Fabric reinforced cementitious mortar (FRCM) materials have started to be employed during the last years with the aim of overcoming the drawbacks related to the use of fibre reinforced polymer (FRP) composites, proving to be potentially suitable for strengthening masonry structures. Moreover, the will to develop materials able to guarantee a certain degree of sustainability without renouncing to adequate mechanical properties has drawn the attention to the use of basalt fibres, which appear to be a valid alternative to carbon or glass fibres. This work presents an experimental investigation on a basalt FRCM (BFRCM) system to confine circular masonry columns, aimed at evaluating the effectiveness of this system in comparison with data obtained by basalt FRP (BFRP) jacketing. A total of eighteen clay brick masonry cylinders were prepared by using two different assembling schemes and subjected to uniaxial compression. Six cylinders were tested as control specimens, while the rest were reinforced by using either one or two layers of basalt textile. Traditional measuring instruments were integrated with the digital image correlation (DIC) technique. The experimental results are presented in terms of stress–strain curves, and strength and strain enhancements of confined cylinders compared to control specimens. The failure modes are also discussed. All outcomes are compared to those obtained by the authors in a similar study performed on BFRP-confined cylinders realized with the same manufacturing in order to have an effective comparison.